Kemandirian Belajar Siswa Pada Penggunaan Platfrom Guru Pembelajar Dalam Pembelajaran Sejarah Di Kelas XI IPS SMA IT Pesantren Nururrahman - Nastiti Zahra Sekarrini, - (2023)
This research is motivated by the low interest of students in learning history, the difficulty of student in finding relevant sources and teachers who have not been able to facilitate students' independent learning activities. The purpose of this research of to describe the achievement of student' learning independence by using the learner teacher platform. In this study, researchers used descriptive qualitative with ethnographic methods, data collection techniques were carried out by observation, interviews and documentation studies. The research interviews were conducted with sources of history teacher and students of XI IPS 1 and XI IPX 2 classes as many as five people each. The result of this study are first, the reason for the history teacher to use this platform is based on the needs of the teacher in learning during online learning and the demands of teacher to master technology and as a forum for student to be able to repeat themselves through independence learning. Second, the learning independence of student using the guru pembelajar platform is well achieved. Third, teacher can overcome the obstacles that occur in using the Guru Pembelajar platform. Thus, the researcher will provide recommendations to the school to further facilitate teacher in using and developing more innovative learning media, and for teacher to optimize the use of the Guru Pembelajar platform in learning history.